Environment and International Studies - Morales-Camacho, María Fernanda (2023)
The environment is a topic that has been analyzed within International Studies. However, its relevance within the discipline has increased in the last 30 years. This thematic issue, 96.2, explores the environment's international dimension. This aims to contribute with theoretical and empirical analysis of complex environmental phenomena beyond the local or national arena, which become issues of global concern.